Use of micropulse laser in patients with diabetic macular edema at the department of ophthalmology, university hospital Hradec Králové - Veselá, Šárka; Hejsek, Libor; Stěpanov, Alexandr; Dusová, Jaroslava; Marák, Jan; Jirásková, Naďa; Studnička, Jan (Czech and Slovak Ophthalmology, 2018)
Introduction: Diabetic macular edema (DME) is the most frequent cause of decreased vision in patiens with diabetes type 2. DME is caused by increased permeability of macular capillaries. The aim of our study was to retrospectively evaluate the results of micropulse laser treatment, 577 nm wavelength, in pacients with DME with follow-up three months and one year. Methods: The retrospective trial with one year follow-up includes 63 eyes of 37 patients with diabetic macular edema treated from September 2015 to January 2017. Most patients had diabetes type 2 (34 patients), 3 patients had diabetes type 1. Diffuse DME was diagnosed in 54 eyes, focal DME in 9 eyes. Most of the patients (42 eyes) suffered from non proliferative diabetic retinopathy, 21 eyes showed signs of proliferative retinopathy. DME lasted on average for 29 months before initiating with micropulse laser (median 21 months). On average 1,56 laser visits were needed for the treatment of 1 eye, usually in 3 months interval. Photocoagulation of macula was performed in all patients by micropulse laser, 577 nm wavelenght/IQ 577TM IRIDEX). We used 5 % duty cycle. The average glycated hemoglobin in the group was 66,8 mmol/mol, maximal 100 mmol/mol. Estimated data were statistically evaluated by Friedman and Dunn´s test. Results: At the end of 1 year period we found out improvement in BCVA (increase of at least 5 letters of ETDRS charts) in 20 eyes, 25 eyes showed stabilisation of BCVA (alltogether 71 % of the group), in 18 eyes we found out decrease of BCVA of more than 5 letters of ETDRS charts. On average we estimated decrease of visual acuity from 62 to 61,1 letters (p > 0,05). After one year we estimated 63 μm CRT decrease on average, from 442 μm to 379 μm (p= 0,0124). Conclusion: In our group of DME patiens treated by micropulse laser we have estimated BCVA stabilisation and signifiant improvement of macular edema in ¾ eyes, confirmed by OCT. We have estimated clinically significant decrease of macular edema in the whole group with one-year follow-up.
Keywords: makulární edém; Visual Acuity; Radiation Dosage; Macular Edema; retrospektivní studie; Humans; zisk písmen; lidé středního věku; laserová terapie; Middle Aged; Diabetes Complications; centrální retinální tloušťka; Glycated Hemoglobin; mikropulzní laser; optická koherentní tomografie; Fundus Oculi; zraková ostrost; mužské pohlaví; diabetes mellitus 2. typu; retina; Laser Therapy; fundus oculi; Tomography, Optical Coherence; komplikace diabetu; Diabetic Retinopathy; Statistics as Topic; výsledek terapie; Diabetes Mellitus, Type 1; Laser Coagulation; Treatment Outcome; diabetes mellitus 1. typu; diabetická retinopatie; Diabetes Mellitus, Type 2; statistika jako téma; laserová koagulace; lidé; glykovaný hemoglobin; dávka záření; Male; Retrospective Studies; Retina